2022
DOI: 10.3389/fmicb.2022.846954
|View full text |Cite
|
Sign up to set email alerts
|

Formation, Transmission, and Dynamic Evolution of a Multidrug-Resistant Chromosomally Integrated Plasmid in Salmonella Spp.

Abstract: IncHI2 plasmids, possessing high flexibility and genetic plasticity, play a vital role in the acquisition and transmission of resistance determinants. Polymorphic mobile genetic elements (MGEs) generated by a chromosomally integrated IncHI2 plasmid in an individual Salmonella isolate have not yet been detected, and the mechanisms of the formation, excision, and dynamic evolution of a multidrug-resistant chromosomally integrated plasmid (MRCP) have remained obscure. Herein, we identified a 260-kb blaCTX–M–55-qn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(66 reference statements)
1
2
0
Order By: Relevance
“…The complete chromosomes and plasmids of these isolates were obtained using a hybrid assembly strategy and single-read analysis, as described in our previous study ( Li et al., 2018 ). According to the assembly results, we found two chromosomally integrated IncHI2 plasmids from isolates SC2016025 and SC2016090 as a similar phenomenon previously reported ( Figures 2A, D ) ( Chang et al., 2022 ). Similar mcr-1 -bearing IncHI2/HI2A plasmids were found in other mcr-1 positive isolates from our investigation including SC2017030, SC2017100, SC2017297 and SC2017167.…”
Section: Resultssupporting
confidence: 90%
“…The complete chromosomes and plasmids of these isolates were obtained using a hybrid assembly strategy and single-read analysis, as described in our previous study ( Li et al., 2018 ). According to the assembly results, we found two chromosomally integrated IncHI2 plasmids from isolates SC2016025 and SC2016090 as a similar phenomenon previously reported ( Figures 2A, D ) ( Chang et al., 2022 ). Similar mcr-1 -bearing IncHI2/HI2A plasmids were found in other mcr-1 positive isolates from our investigation including SC2017030, SC2017100, SC2017297 and SC2017167.…”
Section: Resultssupporting
confidence: 90%
“…The chromosomally integrated plasmid was 330, 232 bp in length and was designated as PSC2020597-sul4-330 k-c ( Figure 1A ). The phenomenon that plasmid was integrated into chromosome have been frequently reported ( Muthuirulandi Sethuvel et al, 2021 ; Shigemura et al, 2021 ; Chang et al, 2022 ), especially in Salmonella , and is commonly mediated by homologous recombination of ISs. We found that PSC2020597-sul4-330 k-c was flanked by IS 1F on chromosome of SC2020597.…”
Section: Resultsmentioning
confidence: 99%
“…By the genetic analysis, we found that sul4 was located on a chromosomally integrated plasmid. However, a previous study demonstrated that chromosomally integrated plasmids could also be transferred to other recipients by conjugation assay ( Chang et al, 2022 ). Here, we verified that there is a circle form of chromosomally integrated plasmid PSC2020597-sul4-330 k-c in some clones of SC2020597 using the inverse PCR method and confirmed by Sanger sequencing ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, ISApl1 was lost entirely in mcr-1 plasmids in isolates of E. coli [106,154], Rauoltella planticola [85], and E. fergusonii [163], wherein it was replaced upstream of mcr-1 by pap2-a gene speculated to be compensating for phospholipid metabolism functions altered during LPS modification by COL resistance determinants [245]-and downstream by the nikB gene. This implies that the loss of ISApl1 does not hinder the transmission of the mcr gene.…”
Section: Eastern Asia Chinamentioning
confidence: 99%